(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Global Manufacturing Virtual Networks (GMVNs) are very dynamic organizations that establish horizontal and vertical relationships between them, where it isno longer necessary to maintain internally large manufacturing resources but efficiently manage and share the network resources. This paper proposes a solid framework where network actors can develop their strategy by avoiding conflicts within these GMVNs formed by three strategic perspectives: 1) nodal, 2) dyadic and 3) systemic.